Soil Erosion and Carbon Dynamics. - Roose, Eric J.; Lal, Rattan; Feller, Christian; Barthes, Bernard; Stewart, B. A. (Milton : Taylor & Francis Group, 2005)
The most complete, nonpartisan source of information on this hot agronomic topic available today, this book brings together a diverse group of papers and data to resolve the debate between sedimentologists and soil scientists and agronomists over whether the effects of soil erosion on carbon and atmospheric CO2 is beneficial or destructive.
Chapter 14: Soil and Carbon Losses under Rainfall Simulation from Two Contrasting Soils under Maize-Improved Fallows Rotation in Eastern Zambia -- Section 3: Carbon Transfer in Rivers -- Chapter 15: Origins and Behaviors of Carbon Species in World Rivers -- Chapter 16: Carbon, Nitrogen, and Stable Carbon Isotope Composition and Land-Use Changes in Rivers of Brazil -- Chapter 17: Organic Carbon Transported by the Equatorial Rivers: Example of Congo-Zaire and Amazon Basins -- Chapter 18: Soil Carbon Stock and River Carbon Fluxes in Humid Tropical Environments: The Nyong River Basin (South Cameroon) -- Chapter 19: Organic Carbon in the Sediments of Hill Dams in a Semiarid Mediterranean Area -- Chapter 20: Monitoring Soil Organic Carbon Erosion with Isotopic Tracers: Two Case Studies on Cultivated Tropical Catchments with Steep Slopes (Laos, Venezuela) -- Section 4: Conclusions -- Chapter 21: Erosion and Carbon Dynamics: Conclusions and Perspectives -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books